Corn Cost-Return Budget in Southeast Kansas - Fogleman, Sarah L.; Kilgore, Gary L. (My University, 2005)
This publication outlines the expected costs and returns for corn in southeast Kansas.
MF993_2005_10
Keywords: MF993; Economics; Crops; MF